Differences in pigmentation between life cycle stages in Scrippsiella lachrymosa (dinophyceae). Issue 1 (7th December 2015) - Persson, Agneta; Smith, Barry C.; Cyronak, Tyler; Cooper, Emily; DiTullio, Giacomo R.
Abstract : Various life cycle stages of cyst‐producing dinoflagellates often appear differently colored under the microscope; gametes appear paler while zygotes are darker in comparison to vegetative cells. To compare physiological and photochemical competency, the pigment composition of discrete life cycle stages was determined for the common resting cyst‐producing dinoflagellate Scrippsiella lachrymosa . Vegetative cells had the highest cellular pigment content (25.2 ± 0.5 pg · cell −1 ), whereas gamete pigment content was 22% lower. The pigment content of zygotes was 82% lower than vegetative cells, even though they appeared darker under the microscope. Zygotes of S. lachrymosa contained significantly higher cellular concentrations of β‐carotene (0.65 ± 0.15 pg · cell −1 ) than all other life stages. Photoprotective pigments and the de‐epoxidation ratio of xanthophylls‐cycle pigments in S. lachrymosa were significantly elevated in zygotes and cysts compared to other stages. This suggests a role for accessory pigments in combating intracellular oxidative stress during sexual reproduction or encystment. Resting cysts contained some pigments even though chloroplasts were not visible, suggesting that the brightly colored accumulation body contained photosynthetic pigments. The differences in pigmentation between life stages have implications for interpretation of pigment data from field samples when sampled during dinoflagellate blooms.